Electrophysiological evaluation of carpal tunnel syndrome female patients after vitamin D replacement - Hikmet SAÇMACI; Nermin TANIK; Özlem BALBALOĞLU; Tülin AKTÜRK; Levent Ertuğrul İNAN (Arquivos de Neuro-Psiquiatria)
Abstract Objective: The effects of vitamin D on the central and peripheral nervous system continue to be investigated today. In the present study, we aimed to evaluate pain and electrophysiologic response in patients with carpal tunnel syndrome (CTS) who have undergone replacement therapy due to vitamin D deficiency. Methods: Fifty female patients diagnosed with mild and moderate CTS and accompanied by vitamin D deficiency were included in this study. Nerve conduction study (NCS) was performed before and after vitamin D replacement, and the patient’s pain was evaluated with Visual Analogue Scale (VAS). Results: When NCS were compared before and after treatment, there was a statistically significant improvement in the median distal sensory onset latency (DSOL) and sensory conduction velocity (CV) and motor distal latencies (DML) values (p=0.001; p<0.001; p=0.001, respectively). At the same time, there was a decrease in the VAS values in patients (p<0.001). When the two groups were compared there was an improvement in DSOL and sensory CV in both groups, but in DML only in moderate CTS group. Conclusion: In this study, it was shown that mild and moderate CTS patients had an improvement in pain and electrophysiological parameters after vitamin D replacement. Replacing vitamin D in early stages of CTS may be beneficial.